Identification of chemical forms of lead, cadmium and nickel in sewage sludge of waste water treatment facilities - Yaman, M; Bakirdere, S (Springer Wien, 2003)
Lead, cadmium and nickel levels in sewage sludge of a waste water treatment facility were determined by slotted tube atom trap (STAT)-flame atomic absorption spectrometry after using different extraction reagents. In addition, a sequential extraction procedure was applied to the same samples and the results were compared. It was found that Pb and Cd were relatively mobile as organically bound, carbonate or adsorbed on the Fe-Mn oxides and the concentrations in the extracts were higher than 50%. However, the percentage of Ni bound to these phases was found to be very low.
Keywords: cadmium; lead; nickel; sewage sludge; AAS; speciation